DINAMIKA INTERAKSI ANTARETNIK DALAM MEWUJUDKAN KESERASIAN SOSIAL DI WILAYAH PERBATASAN NEGARA INDONESIA – MALAYSIA - Agus Sikwan (JURNAL SOSIAL HUMANIORA (JSH), 2017)
The research reveals the dynamics of interaction between the three major ethnic groups (ethnic Dayak, Malay and Chinese) living in Entikong Subdistrict. These interactions are manifested in social relationships, ie relationships as relatives, as friends. Through qualitative analysis, the relationship is still strong in primordial loyalty among ethnic groups. It is characterized by a tendency to choose individuals from their own ethnic groups to serve as relatives. The results also show that there are two forms of ethnic group settlements in Entikong Subdistrict, namely: Mixed pattern, ie settlement area in which consists of various ethnic groups, in which there is more intensive inter-ethnic social contact that can encourage the realization of harmony social; Separate pattern, ie settlement area which consists of oneethnic group of the same kind, generally inhabited by Chinese ethnic groups. The change of settlement pattern indirectly caused by the expansion of subdistricts and population growth